The importance of the relationship between chronic periodontitis and chronic obstructive pulmonary disease - Tamás Tián; István Gorzó; Gábor Ősze; Attila Somfay; Márta Radnai (Hungarian Dental Association, 2021)
Periodontitis is one of the most common human chronic inflammatory diseases and about 11% of adults develop its clinical signs. Untreated periodontitis ultimately leads to inflammation and destruction of the periodontium leading to the loss of the teeth. Periodontitis is considered as a dental focal infection. The foci can influence other diseases in different areas of the body through different pathways. Diseases and conditions such as cardiovascular disease, diabetes mellitus, rheumatoid arthritis, gastric ulcer, pregnancy complications and respiratory diseases such as aspiration pneumonia and chronic obstructive pulmonary disease (COPD) have been proven to be affected by the condition of the periodontium. COPD is an inflammatory disease characterized by progressive deterioration of pulmonary function and increasing airway obstruction, including chronic bronchitis and emphysema. It has a worldwide prevalence in adults at the age of 40 years or older in about 9%-10%, and it is currently the third leading cause of death worldwide. In addition, the incidence and mortality of COPD are continually increasing. An observational study found that 97% of a COPD cohort had at least one other comorbidity, with 50% having at least four. This impacts the health care costs of COPD patients with multiple comorbidities that are 4,7 times higher than those with no comorbidity. As periodontitis and COPD are both chronic, progressive conditions characterized by neutrophilic inflammation with subsequent proteolytic destruction of connective tissue, it has been proposed that they share common pathophysiologic processes. Several mechanisms have been proposed to explain the association of periodontal disease and COPD. As summarized by the European Federation of Periodontology and American Academy of Periodontology (EFP/AAP), COPD inflammatory status may be modified either by aspiration of bacteria from the oral cavity and/or haematogenous dissemination of inflammatory mediators and plaque organisms from periodontal pockets. The present review of literature aims to investigate the potential connection between periodontal disease and COPD.